Step-by-step explanation:
Let the number be x.
<u>1</u><u> </u> =8 + x
6
6×<u>1</u>=6×8+6×x
6
1=48+6x
1-48=6x
<u>-</u><u>4</u><u>7</u>=<u>6</u><u>x</u>
6. 6 x = -7 <u>5</u>
6
x is equal to minus seven whole number five divided by six.
Answer:
Numbers =(6,-2 )
Step-by step explanation:
Given
the sum of two numbers is four and the sum of their squares minus three times their product is 76,
Let the first term =X
Second term will be=4-x
So
X^2+(4-x)^2-3x(4-x)=76
x^2+16+x^2-8x-12x+3x^2=76
5x^2-20x+16=76
5x^2-20x-60=0
5(x^2-4x-12)=0
So x^2-4x-12=0
x^2-(6-2)x-12=0
x^2-6x+2x-12=0
X(x-6)+2(x-6)=0
(X-6)(X+2)=0
X=6,-2
Let X=6 and -2 then numbers will be 6 and (4-6)=-2
It is 1.55 times the value of the second number.
Answer:
7t^2 + 21t
Step-by-step explanation:
You have 7 tiles of each t by t+3.
One tile has an area of
t * (t+3) = t^2 + 3t
So in total the area is
7* (t^2 + 3t)
7t^2 + 21t